2020
DOI: 10.1021/acs.jafc.0c00542
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Bioaccumulation of 6:2 Fluorotelomer Sulfonate, 6:2 Chlorinated Polyfluoroalkyl Ether Sulfonates, and Perfluorophosphinates in a Soil–Plant System

Abstract: As emerging alternatives of legacy perfluoroalkyl substances, 6:2 fluorotelomer sulfonate (6:2 FTS), 6:2 chlorinated polyfluoroalkyl ether sulfonates (6:2 Cl-PFESA), and perfluorophosphinates (C6/C6 and C8/C8 PFPiAs) are supposed to be partitioned to soil and highly persistent in the environment. The uptake of novel per-and polyfluoroalkyl substances (PFASs) by plants represents a potential pathway for their transfer in the food chain. In this study, the bioavailability of these four novel PFASs in soil and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…However, given the relatively high accumulation of PFNA and PFDS in the plant roots (Figure S5), it can be assumed that sorption to plant roots is a critical function of PFNA and PFDS accumulation. This is in agreement with numerous studies that have observed an increased accumulation of PFAS with increased chain length. ,,, This is presumably due to their increased attraction to the root lipids and inability to cross the Casparian strip. ,,,, However, further research is needed to understand the accumulation mechanisms of PFNA and PFDS in plants.…”
Section: Resultssupporting
confidence: 89%
“…However, given the relatively high accumulation of PFNA and PFDS in the plant roots (Figure S5), it can be assumed that sorption to plant roots is a critical function of PFNA and PFDS accumulation. This is in agreement with numerous studies that have observed an increased accumulation of PFAS with increased chain length. ,,, This is presumably due to their increased attraction to the root lipids and inability to cross the Casparian strip. ,,,, However, further research is needed to understand the accumulation mechanisms of PFNA and PFDS in plants.…”
Section: Resultssupporting
confidence: 89%
“…As a type of surfactant, the target PFASs may change the permeability of the cell membrane, which would promote plant uptake of nutrient elements such as magnesium and nitrogencrucial components of the chlorophyll molecule. Eventually, the shoot biomass would be enhanced, possibly due to the rise of the chlorophyll content. ,,,, The HFPO homologues and PFOA were not found in the roots and shoots of the control group (Table S2), suggesting that their uptake from endogenous sources and foliar uptake were negligible. Generally, the root concentrations were as follows: PFOA ≥ HFPO-DA > HFPO-TA > HFPO-TeA for both LT and HT (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, the shoot biomass would be enhanced, possibly due to the rise of the chlorophyll content. 25,26,31,32,40 The HFPO homologues and PFOA were not found in the roots and shoots of the control group (Table S2), suggesting that their uptake from endogenous sources and foliar uptake were negligible. Generally, the root concentrations were as follows: PFOA ≥ HFPO-DA > HFPO-TA > HFPO-TeA for both LT and HT (Figure 1).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations